Impactos ambientais: emissão de gases poluentes por veículos automotores na Av. Luís Vianna Filho - CARVALHO, Luiz Augusto Hegouet (2014)
The unplanned urban expansion, the growth of the motor vehicle fleet, energy matrix supported by fossil fuels, noncompliance with regulatory processes maintenance, inspection and enforcement and non-renewal of the fleet have been factors in the increased concentration of greenhouse gases in the atmosphere. By assumptions, we sought to characterize the interfaces between the concentrations recorded rates of air pollutants and alternatives to minimize the negative impacts a major traffic corridors and housing boom soteropolitana, Av. Luis Vianna Filho. We used public data issued by CETREL, obtained from air quality monitoring station, the period between the years 2012 and 2013. It was observed that the concentrations of pollutants recorded, were within the normal range established by Resolution CONAMA 03/90, considered good, three events happening during this period with regular air quality, highlighting the effectiveness of PROCONVE and PROMOT programs, to establish emission limits for gases, emergence of new technologies and improved fuel quality. Note the need for planning and prevention in relation to emission of pollutants, in order to ensure a good air quality for the benefit of urban citizens, the need for public policies are swarming - of different orders that impact multiple simultaneous aspects on issues, urban pollution , urban mobility and public health, whose actions can be summarized as follows : priority of a public transport quality, increasing restriction on movement of individual motor vehicles, encouraging urban solutions favoring the use of non-motorized transport, greater greenhouse gas emission control and inspection program vehicular. These actions will provide the maintenance of pollutant emissions standards, at the same time which will contribute to the benefits of quality of life and health.